2008
DOI: 10.1007/s10295-008-0356-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening of tropical fungi producing polyethylene terephthalate-hydrolyzing enzyme for fabric modification

Abstract: Microfungi were selectively isolated for production of polyethylene terephthalate (PET) fiber-degrading enzymes potentially to be used to modify the surface of polyester fabric. A range of fungi were isolated from plant surfaces and soil samples using a polycaprolactone (PCL) plate-clearing assay technique, and screened for cutinolytic esterase (cutinase) activity. Twenty-two of 115 isolates showed clearing indicating the production of cutinase. The ability of the fungi to produce cutinase in mineral medium (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Cutinase is one of these enzymes, and cutinases from F. solani f. sp. pisi (6,10,26,36), F. oxysporum (25), and T. fusca (1,13,14,24,32) have been well studied regarding PET modification. However, the catalytic efficiencies of these enzymes are not sufficiently high to meet the requirements of the textile industry (10).…”
Section: Resultsmentioning
confidence: 99%
“…Cutinase is one of these enzymes, and cutinases from F. solani f. sp. pisi (6,10,26,36), F. oxysporum (25), and T. fusca (1,13,14,24,32) have been well studied regarding PET modification. However, the catalytic efficiencies of these enzymes are not sufficiently high to meet the requirements of the textile industry (10).…”
Section: Resultsmentioning
confidence: 99%
“…The intent of our study was to isolate and describe a microorganism that can degrade and assimilate poly(ethylene terephthalate) (PET) (2). Therefore, we only cited the pioneering works that report specific microorganisms able to grow on PET (3,4). In a previous study, Sharon and Sharon (5) confirmed microbial PET degradation by semiisolated microorganisms, where the involvement of Nocardia species was implied by microscopic observation.…”
mentioning
confidence: 99%
“…Nimchua et al reported that the agar plate assay for detecting the PET-hydrolysing enzyme of Fusarium spp. showed no correlation between the quantity of enzyme produced and the clearing zone development 15 . All four fungi decolourized wastewater No.…”
Section: Fungal Isolatementioning
confidence: 91%